Energetic and genomic potential for hydrogenotrophic, formatotrophic, and acetoclastic methanogenesis in surface-expressed serpentinized fluids of the Samail Ophiolite - Howells, Alta E. G.; Quinn, Lilja M.; Silva, Miguel G.; Akiyama, Kylie; Fifer, Lucas M.; Boyer, Grayson; Kashyap, Srishti; Robinson, Kirt; Broddrick, Jared; Shock, Everett L.; Hoehler, Tori M. (Frontiers in Microbiology, 2025)
Serpentinization, the reaction of water with ultramafic rock, produces reduced, hyperalkaline, and H2-rich fluids that support a variety of hydrogenotrophic microbial metabolisms. Previous work indicates the occurrence of methanogenesis in fluids from the actively serpentinizing Samail Ophiolite in the Sultanate of Oman. While those fluids contain abundant H2 to fuel hydrogenotrophic methanogenesis (CO2 + 4H2 ➔ CH4 + 2H2O), the concentration of CO2 is very low due to the hyperalkalinity (> pH 11) and geochemistry of the fluids. As a result, species such as formate and acetate may be important as alternative methanogenic substrates. In this study we quantified the impact of inorganic carbon, formate and acetate availability for methanogenic metabolisms, across a range of fluid chemistries, in terms of (1) the potential diffusive flux of substrates to the cell, (2) the Affinity (Gibbs energy change) associated with methanogenic metabolism, and (3) the energy “inventory” per kg fluid. In parallel, we assessed the genomic potential for the conduct of those three methanogenic modes across the same set of fluids and consider the results within the quantitative framework of energy availability. We find that formatotrophic methanogenesis affords a higher Affinity (greater energetic yield) than acetoclastic and hydrogenotrophic methanogenesis in pristine serpentinized fluids and, in agreement with previous studies, find genomic evidence for a methanogen of the genus Methanobacterium to carry out formatotrophic and hydrogenotrophic methanogenesis, with the possibility of even using bicarbonate as a supply of CO2. Acetoclastic methanogenesis is also shown to be energetically favorable in these fluids, and we report the first detection of a potential acetoclastic methanogen of the family Methanosarcinaceae, which forms a distinct clade with a genome from the serpentinizing seafloor hydrothermal vent field, Lost City. These results demonstrate the applicability of an energy availability framework for interpreting methanogen ecology in serpentinizing systems.